Forest Resources, Government Policy, and Investment Location Decisions of the Forest Products Industry in the Southern United States - Changyou Sun; Daowei Zhang (Forest Science, 2001)
In this article, the results of an initial attempt to estimate the effects of state attributes on plant location and investment expenditure were presented for the forest products industry in the southern United States. A conditional logit model was used to analyze new plant births, and a time-series cross-section model to assess the total capital expenditure. Significant positive effects were found for personal income and forest inventory, and negative effects were found for population density. In the short run, tax and energy costs had negative impacts on new plant births in a state, while in the long run, stumpage price and environmental stringency had negative effects on the capital expenditure. Sensitivity of model specification was documented, and policy implications were discussed. For. Sci. 47(2):169–177.